Temporal and spatial distribution, influencing factors and trend prediction of HIV/AIDS incidence among adolescents in Hubei province: an analysis on surveillance data of 2009 - 2019 - Tao ZHANG; Jinbo YAN; Heng TANG (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo examine temporal and spatial distribution patterns and influencing factors of human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) epidemic among adolescents in Hubei province, and to predict prevalence trend of the epidemic for providing reference to HIV/AIDS epidemic prevention and control in the adolescents. MethodsThe data on registered HIV/AIDS incident cases aged 15 - 24 years in Hubei province from 2009 through 2019 were collected from Hubei Provincial Center for Disease Control and Prevention and analyzed statistically with spatial autocorrelation, geographically weighted regression, geographic detector, and autoregressive integrated moving average (ARIMA) model. Results The HIV/AIDS incidence among the adolescents in the province increased rapidly during the period, with an average annual growth rate of 16.2%. The HIV/AIDS epidemic was the most serious among adolescents living in the central and eastern part of Hubei province, especially in Wuhan city and its surrounding counties and the epidemic spread gradually across the province. Regions with stable high-high clustering of the epidemic were observed in urban Wuhan and its surrounding areas. The regions with high clustering of the epidemic distributed generally from northwest to southeast of the province during the period. The incidence of HIV/AIDS in the adolescents was affected by natural and social factors and there were differences in the intensity and spatial distribution of the factors including traffic network density, population density, the number of schools, number of medical and health institutions, urbanization rate, altitude, and gross domestic product per capita ranking in downward order of the effect intensity of the factor. Both the population density and the traffic network density have a positive effect on the epidemic. The interaction between influencing factors plays an important role in promoting the spread of the epidemic. When any two influencing factors interact with each other, their influence will be enhanced interactively or nonlinearly. Based on the result of ARIMA analysis, the HIV/AIDS epidemic could be more serious among the adolescents in the province during 2020 - 2023, especially in urban Wuhan and some other prefectures. ConclusionThe HIV/AIDS epidemic was spreading among adolescents in Hubei province during 2009 - 2019, suggesting that relevant education and intervention should be strengthened in the population.